High Asparatate Aminotransferase Level Predicts Poor Neurodevelopmental Outcome in Infants with Meconium Aspiration Syndrome - Chen, I-Lun; Ou-Yang, Mei-Chen; Chen, Feng-Shun; Chung, Mei-Yung; Chen, Chih-Cheng; Huang, Hsin-Chun (American Journal of Perinatology, 2014)
Objective The aim of our study is to clarify the perinatal predictive factors of meconium aspiration syndrome (MAS) with neurodevelopmental delay (ND) in infants.Materials and Methods In this retrospective study, data were collected from the infants born between 1990 and 2008. They all had primary diagnosis of MAS. Multivariable analyzed perinatal predictive factors of MAS with ND. The developmental status of these infants was followed at least 2 years with the Wechsler Intelligence Scale for Children.Results A total of 114 surviving babies met the criteria of MAS. Six babies were defined as ND group. Lower 5-mintue Apgar score and diastolic blood pressure were significantly related to the ND group. Elevated asparatate aminotransferase (AST), nucleated red blood cells, and white blood cells at the time of admission were significantly high in ND group. Furthermore, AST had area under the receiver operating characteristic curve of 0.879, (95% confidence interval: 0.801, 0.934), p < 0.0001. At 96 mg/dL, it had 83.33% sensitivity, 80.81% specificity, and negative predictive value of 98.8. Multivariable logistic regression analysis revealed AST was the only significant predictive factor for MAS with ND.Conclusion Early intervention should be recommended in infants having MAS with high AST level at birth for improving their neurodevelopmental outcomes.
Keywords: asparatate aminotransferase; meconium aspiration syndrome; neurology; liver